2012
DOI: 10.1186/2191-219x-2-54
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a novel radioiodinated vesamicol analog as a sigma receptor imaging agent

Abstract: BackgroundSigma receptors are highly expressed in human tumors and should be appropriate targets for developing tumor imaging agents. Previously, we synthesized a vesamicol analog, (+)-2-[4-(4-iodophenyl)piperidino]cyclohexanol ((+)-pIV), with a high affinity for sigma receptors and prepared radioiodinated (+)-pIV. As a result, (+)-[125I]pIV showed high tumor uptake in biodistribution experiments. However, the accumulation of radioactivity in normal tissues, such as the liver, was high. We supposed that some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The reaction mixture was rotated for 1 h, and 1 mL of methanol was added to react for another 30 min. Next, the peptide chain was constructed in cycles of (I) 15 To cleave peptides from the resin, the resin-bound peptides were treated with 30% HFIP in dichloromethane for 5 min. After filtration, the solvent in the filtrate was removed in vacuo.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reaction mixture was rotated for 1 h, and 1 mL of methanol was added to react for another 30 min. Next, the peptide chain was constructed in cycles of (I) 15 To cleave peptides from the resin, the resin-bound peptides were treated with 30% HFIP in dichloromethane for 5 min. After filtration, the solvent in the filtrate was removed in vacuo.…”
Section: Resultsmentioning
confidence: 99%
“…[2-[2-(tert-Butyloxycarbonyl) aminoethoxy] ethoxy] acetic acid (Boc-NH-EG 2 -COOH) (14) was prepared in 4 steps (5%) from 2-[2-(2-chloroethoxy) ethoxy] ethanol using a method described previously. (13), which was synthesized using a method described previously, 24) was dissolved in 100 µL of DMF.…”
Section: Mg 35%) Esi-ms M/z: 746 ([M+h]mentioning
confidence: 99%
See 2 more Smart Citations
“…Ogawa and colleagues evaluated radioiodinated vesamicol analogs for tumor imaging and antitumor activity (42,43). They found that radioiodinated vesamicol analogues suppressed the growth of human prostate cancer cells in mice model.…”
Section: Discussionmentioning
confidence: 99%